Design and optimization of torsion harvester of Lycium barbarum L. - Chen, Qingyu; Zhang, Shixia; Wei, Naishuo; Li, Puhang; Hu, Guangrui; Chen, Jun; Chen, Yu (International Journal of Agricultural and Biological Engineering, 2024)
The production of Lycium barbarum L. is a labor-intensive industry. Multiple manual harvests are required during the harvesting season, which contributes to the high harvesting costs. The cultivation conditions of L. barbarum were investigated to increase efficiency and mitigate harvesting damage. A torsion harvester was designed according to the characteristic of infinite inflorescence and the distribution of detachment force, and the kinematics model of the harvester was established. The vibration responses of ripe and unripe fruit were obtained through ADAMS simulation of the branch model, and the influencing factors and value range of the torsion harvester were also determined. The mathematical models of ripe fruit harvesting rate, unripe fruit harvesting rate, ripe fruit damage rate and torsion angle, vibration rods distance, and vibration frequency were established by the Box-Behnken test. The influences of various factors on ripe fruit harvesting rate, unripe fruit harvesting rate, and ripe fruit damage rate were analyzed, and the best parameter combination was obtained: torsion angle 73.66°, vibration rods distance 35.51 mm and vibration frequency 19.12 Hz. Field experiment showed that the harvesting rate of ripe fruit is 95.67%, the harvesting rate of unripe fruit is 4.68%, and the damage rate of ripe fruit is 3.70%. The research results can promote the mechanization process of L. barbarum harvest, and provide a reference for vibration harvest of berries. Key words: L. barbarum; vibrating; torsion; response surface method; parameters optimization; ADAMS; RSM DOI: 10.25165/j.ijabe.20241704.8082 Citation: Chen Q Y, Zhang S X, Wei N S, Li P H, Hu G R, Chen J, et al. Design and optimization of torsion harvester of Lycium barbarum L. Int J Agric & Biol Eng, 2024; 17(4): 109–115.